2005
DOI: 10.1007/s10549-004-5328-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metastasis by inhibition of tumor-derived CCL5

Abstract: To determine whether tumor-derived CCL5 contributes to the metastatic potential of murine mammary carcinoma, we used the 4T1 tumor which spontaneously metastasizes and constitutively produces CCL5. Mice bearing 4T1 that expressed less CCL5 had significantly fewer lung and liver metastasis. The decrease in tumor-derived CCL5 also correlated with decreased cathepsin L, MMP-2, MMP-3, MMP-10 and MMP-17 gene expression. Thus, inhibition of tumor-derived CCL5 can impact the metastatic capability of 4T1 and may do so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 17 publications
4
34
0
2
Order By: Relevance
“…CCL5 and its receptors, including CCR1, CCR3, and CCR5, have been previously reported to play an important role in tumor invasion and metastasis [25,26]. Interestingly, with cells from the A2780 origin, we found that CSLCs have an elevated level of expression of not only all three CCL5 receptors but also CCL5 itself.…”
Section: Ccl5 Is Required For Invasion and Migration Of Cslcsmentioning
confidence: 53%
See 1 more Smart Citation
“…CCL5 and its receptors, including CCR1, CCR3, and CCR5, have been previously reported to play an important role in tumor invasion and metastasis [25,26]. Interestingly, with cells from the A2780 origin, we found that CSLCs have an elevated level of expression of not only all three CCL5 receptors but also CCL5 itself.…”
Section: Ccl5 Is Required For Invasion and Migration Of Cslcsmentioning
confidence: 53%
“…Matrix metalloproteinases (MMPs) are enzymes that degrade the extracellular matrix and play a pivotal role in metastatic processes. MMP-9 has been implicated in many types of cell translocation, including invasion of tissues by tumor cells, T cells, and dendritic cells [26,27]. Furthermore, it has been postulated in previous studies that MMP-9 is involved in CCL5-directed cell migration [27,28,29].…”
Section: The Superior Migration and Invasion Of Cslcs Is Dependent Onmentioning
confidence: 99%
“…CCL5 has also been shown to be a significant predictor of progression in patients with stage II breast cancer (Hahoshen et al 2006). In another study, tumors that expressed higher levels of CCL5 were more likely to metastasize in comparison with tumors that did not express as much CCL5 (Stormes et al 2005). Vaday et al (2006), in another recent study, have shown that CCL5 increases the proliferation and growth of prostate cancer cells.…”
Section: To the Editormentioning
confidence: 95%
“…Since CCL5 was previously found to be involved in the migration and progression of breast cancer (6,11,(24)(25)(26), we further inestigated how ER stress-induced upregulation of CCL5 affects the transmigration of MCF-7 cells. Tunicamycin inhibited the transmigration of MCF-7 to 27% of the control (P<0.01), which was antagonised by 4-PBA treatment, while the transmigration index of cells treated with both tunicamycin and 4-PBA was reverted to 61% of the control (P<0.05), and 4-PBA treatment alone had no effect on the transmigration of MCF-7 cells (Fig.…”
Section: Er Stress-induced Ccl5 Upregulation Is Positively Correlatedmentioning
confidence: 99%
“…Expression of CCL5 is upregulated in breast cancer, and is correlated to disease progression (7,8). Elevated CCL5 in tumours promotes cell motility, migration, invasion and metastasis (9,10) and inhibition of tumour-derived CCL5 attenuates the metastasis of tumours (11).…”
Section: Introductionmentioning
confidence: 99%